Strategi Pengembangan Sumber Daya Manusia Dalam Meningkatkan Kinerja Tenaga Kependidikan Sekolah Tinggi Ilmu Ekonomi Balikpapan Melalui Siakad 4.0 - Anhar Anhar; Megawaty Megawaty; Novita Rosanti (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
This research explores the implementation of human resource development strategies in enhancing the performance of educational staff through the deployment of Academic Information System version 4.0 at Sekolah Tinggi Ilmu Ekonomi Balikpapan. Employing a qualitative descriptive method with a case study approach conducted during April-May 2025, the study involved 10 informants selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation analysis, subsequently analyzed using the Miles & Huberman interactive model with NVivo 12 Plus software. The findings demonstrate that Siakad 4.0 implementation significantly enhanced work efficiency. Human resource development strategies encompassing technical training, soft skills development, and managerial competency strengthening contributed substantially to successful system adaptation. Primary supporting factors included management support, system quality, and organizational learning culture. However, challenges emerged including interface complexity, limited continuous training opportunities, and change resistance. The research underscores the critical importance of integrating human resource development with information technology for higher education organizational transformation..